Internet Addiction among Undergraduate Students: Evidence from a Malaysian Public University - A.M., Rosliza; M.N., Ragubathi; M.K.A, Mohamad Yusoff; M.S., Shaharuddin (IIUM Medical Journal Malaysia, 2020)
Introduction: Internet addiction is an increasingly worrying phenomena affecting people globally especially the youths. This study aimed to determine the prevalence of internet addiction among undergraduate students in a Malaysian public university and its associated factors. Materials and Methods: A cross-sectional study involving 322 undergraduate students, identified through cluster sampling was conducted using a pretested, self-administered questionnaire. The questionnaire includes socio-demography, use of information technology gadgets and internet usage. Internet Addiction test (IAT) was used to identify internet addiction. Data was analysed using SPSS version 22. Results: From 322 respondents, 25 (7.8%) were categorised as addictive internet users, while 182 (56.5%) were problematic internet users. The commonest online activity includes social networking (86.6%), entertainment (77.3%) and educational purposes (77.0%). From multivariate analysis, problematic and addictive internet use was significantly more common among male students (AOR=2.47, 95% CI [1.43, 4.26]), those who received study loan (AOR=1.93, 95% CI [1.10, 3.39]) and other types of funding (AOR=3.95, 95% CI [1.59, 9.80]) compared to those on scholarships, and those who spent between four to ten hours a day accessing the Internet (AOR=2.43, 95% CI [1.13, 5.23]) compared to those using the Internet for two hours or less a day. Conclusion: The prevalence of problematic and addictive internet use among respondents were higher compared to previous researches among Malaysian adolescents. It is recommended that an awareness programme on responsible use of the internet be conducted to prevent students from becoming addicted which may impact negatively on their educational performance and social life.